2014
DOI: 10.1038/srep07040
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and epidemiological insights into the emergence of peste des petits ruminants virus (PPRV) across Asia and Africa

Abstract: Small ruminants are important components in the livelihood of millions of households in many parts of the world. The spread of the highly contagious peste des petits ruminants (PPR) disease, which is caused by an RNA virus, PPRV, across Asia and Africa remains a major concern. The present study explored the evolutionary and epidemiological dynamics of PPRV through the analyses of partial N-gene and F-gene sequences of the virus. All the four previously described PPRV lineages (I-IV) diverged from their common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
21
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 53 publications
3
21
2
Order By: Relevance
“…Accordingly, the evolutionary rate of PPRV at the genomic scale was estimated to be 7.8 × 10 −4 nucleotide substitutions per site, per year (95% HPD values = 7.3–8.4 × 10 −4 subs/site/year) and the time to common ancestor of this sample of PPRV was estimated to be between 1891–1905 (95% HPD values). These rate and divergence time estimates are broadly similar to those estimated previously for PPRV (Muniraju et al., ; Padhi and Ma, ), although for our analysis we has used a larger number of full genome sequences which have become available since their publications. Similarly, the divergence time of the genotype II viruses (of which Benin/B1/1969 is the basal lineage) was estimated to be between 1960–1963, while Benin/10/2011 is estimated to have diverged from Ghana/2010 and SnDK/Senegal/2013 between 1996–1999.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…Accordingly, the evolutionary rate of PPRV at the genomic scale was estimated to be 7.8 × 10 −4 nucleotide substitutions per site, per year (95% HPD values = 7.3–8.4 × 10 −4 subs/site/year) and the time to common ancestor of this sample of PPRV was estimated to be between 1891–1905 (95% HPD values). These rate and divergence time estimates are broadly similar to those estimated previously for PPRV (Muniraju et al., ; Padhi and Ma, ), although for our analysis we has used a larger number of full genome sequences which have become available since their publications. Similarly, the divergence time of the genotype II viruses (of which Benin/B1/1969 is the basal lineage) was estimated to be between 1960–1963, while Benin/10/2011 is estimated to have diverged from Ghana/2010 and SnDK/Senegal/2013 between 1996–1999.…”
Section: Resultssupporting
confidence: 66%
“…The persistence of lineage II in Benin is of note when compared to other countries/regions in Africa. In Senegal, viruses isolated in the 1960s are from lineage I and have now been replaced by lineage II viruses (Dundon et al, 2015;Kwiatek et al, 2007Kwiatek et al, , 2011Salami et al, 2014). A similar situation has also occurred in Sudan and Ethiopia where lineages III viruses that were present in the 1970-1990s have now been replaced by lineage IV viruses (Kwiatek et al, 2011;Libeau et al, 2014;Muniraju et al, 2016).…”
mentioning
confidence: 90%
“…Phylogenetic analysis revealed that the strain involved in the Ghardaïa outbreak is very close to those identified in Morocco and Tunisia; this is compatible with the recent establishment and spread of the Asian PPRV lineage IV in Africa and its emergence in other parts of Africa (Kwiatek et al 2011;Libeau et al 2014;Padhi and Ma 2014).…”
Section: Discussionsupporting
confidence: 67%
“…Traditionally, lineages I and II are found in West Africa, lineage III in East Africa and the Middle East, and lineage IV in Asia. Recent studies have shown changes in this distribution including the emergence of PPRV lineage IV in northeastern and northern Africa (Kwiatek et al 2011;Albina et al 2013;Libeau et al 2014;Padhi and Ma 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Recent phylogenetic analysis revealed that the Chinese Tibetan strains and the Chinese 2013-2014 strains were separately grouped into two clusters in lineage IV (Wu et al, 2015). Historically, PPRV molecular epidemiology has focused on the partial N (255 nt region; nucleotide site 1360-1614 of PPRV genome) or partial F gene (322 nt region; nucleotide site 5779-6100 of PPRV genome) sequences, preventing the in-depth evolutionary analysis among strains (Cosseddu et al, 2013;Munir et al, 2011;Ozkul et al, 2002;Padhi and Ma, 2014;Soltan and Abd-Eldaim, 2014). Genome sequences for PPRV have recently been used for an evolutionary study on a global scale (Muniraju et al, 2014c).…”
mentioning
confidence: 99%